Framework for practising knowledge management - Armistead, Colin (2002)
Sets out a matrix that describes four approaches to knowledge management based on whether it is in an organizational or an individual context, and whether knowledge management is imposed or empowered by managerial approaches. Explains the validity of the framework through an analysis of ongoing management projects at seven organizations.